Citrus Export Performances of Southeast Asian Countries: A Comparative Analysis - Rahmat Budiarto; Dian Galuh Pratita (Teknotan: Jurnal Industri Teknologi Pertanian, 2022)
Citrus is a popular horticultural commodity worldwide, including in Southeast Asian. This study aimed to comparatively analyze export performances of citrus (limited to lime and lemon) among Southeast Asian countries (ASEAN), that are represented by the top 5 larger exporters, namely Vietnam, Thailand, Indonesia, Malaysia, and Singapore. This study applied several approaches, i.e., RCA (Revealed Comparative Advantage), ECI (Export Competitiveness Index), TSI (Trade Specialization Index), AR (Acceleration Ratio), and EPD (Export Product Dynamics). The secondary data is derived from the International Trade Center from 2010 to 2020. The result showed that those five countries had a low comparative advantage (RCA < 1), but Vietnam had a better performance than other countries. However, Indonesia displayed an upward trend in citrus exports in the last two years (ECI>1). If we look further, Indonesia was still in the initial stage of the citrus export activity to the world market (TSI -0.9), in similar to Singapore and Malaysia, while Vietnam's position was more advanced (TSI 0.9). Indonesia still has a chance to maintain its market share, as indicated by the increased export trend, even though the current condition showed a weak comparative advantage and is still in the initial export stage.